PENGARUH CUSTOMER SERVICE DAN WORD OF MOUTH TERHADAP MINAT BELI KONSUMEN AL AZIZIAH TOUR AND TRAVEL - Baladhika, Nicole Kansa Kostra; Syahputra, Syahputra (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
After the end of the Covid-19 pandemic, the world economy began to show signs of improvement with economic growth in various countries. The economic growth then triggered business development in Indonesia which occurred in various sectors, including the tourism and service sectors such as Hajj and Umrah travel agency companies. With such high competition, Umrah travel organizers need an appropriate way to compete. One of the efforts that can be carried out to compete is to improve the quality of marketing. In obtaining consumers, one of the crucial aspects to keep in mind is the buying interest of Umrah pilgrims, because it can play a role in the success of the Umrah travel agency business. One of the aspects that have an impact on buying interest is service quality, including the customer service section or more commonly referred to as customer service and verbal word of mouth communication or commonly referred to as word of mouth. This study was conducted on Al Aziziah Tour and Travel. Al Aziziah Tour and Travel is a travel agency that organizes umrah in Indonesia. It was founded in 2013 and is headquartered in Bekasi. The purpose of this study is to examine the influence of customer service and word-of-mouth on Al Aziziah's customer purchase intention. A quantitative approach based on a descriptive causal research type was used in this investigation. A total of 325 participants were polled using a non-probability sampling technique. Descriptive statistics and multiple linear regression were employed for data analysis. The data were processed using SPSS Version 23 software. The findings revealed that the customer service factor exhibited a positive and noteworthy impact on purchase intention, with a significance level of 0.000, indicating its significance at a 5% level of significance. The t-value of 7.122 surpassed the t-table value of 1.967. Similarly, the word-of-mouth variable demonstrated a positive and significant influence on purchase intention, with a significance level of 0.000, also surpassing the t-table value with a t-value of 7.435. When considered simultaneously, both customer service and word of mouth significantly affected purchase intention, with a significance level of 0.000 and an F-value of 171.302, exceeding the F-table value of 3.0237. The combined influence of the independent variables, word of mouth, and customer service, accounted for 51.6% of the variation in purchase intention, while the remaining 48.4% was attributed to unexamined factors in this research.